THE BENEFECIAL EFFECTS OF FISH OIL SUPPLEMENTATION ON HYPERLIPIDEMIC AND HYPOTHYROID ALBINO RATS - ABDEL-MONEIM, ADEL; Mahmoud, Basant; Mahmoud, Rania (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Background: Fish oils (FO) contain the omega-3 fatty acids eicosapentaenoic acid, and docosahexaenoic acid, precursors of certain eicosanoids that offering multiple health benefits. Objectives: The current study performed to evaluate the effect of FO administration on hyperlipidemic and hypothyroid albino rats. Methods: Hyperlipidemia was inducted by adding cholesterol powder, cholic acid and animal lard to the standard diet, while hypothyroidism was induced by administration of carbimazole. Hyperlipidemic and hypothyroid rats received FO to rats through gastric intubation. Rats divided into five groups each group contains six rats, and all treatments were performed orally and daily for 6 weeks. Results: The current results revealed that FO administration was increased significantly thyroid hormones concentrations in the serum of hyperlipidemic and hypothyroid rats as compared to control rats. However, leptin hormone concentration recorded a significant decrease by in both groups. Moreover, FO treatment ameliorated significantly the elevated level of lipid parameters in hyperlipidemic rats while treated hypothyroid rats recorded decreased levels of total lipids and atherogenic index only. Moreover, FO treatment ameliorated the non-enzymatic antioxidant, liver malondialdehyde and glutathione (GSH) concentration and the enzymatic antioxidant, liver GSH-S-transferase and catalase activities, and also the cardiac enzymes lactate dehydrogenase and creatine kinase activities in the treated groups. Conclusion: FO administration showed a beneficial therapeutic effect on hyperlipidemic and hypothyroid albino rats due to the presence of omega-3 fatty acids, which showed hypolipidemic, antioxidant and hyperthyroid action. Keywords: Omega 3 fatty acids, Fish oil, Antioxidants, Hyperlipidemia and hypothyroidism.